2015
DOI: 10.3109/23744235.2015.1033003
|View full text |Cite
|
Sign up to set email alerts
|

Two-year prospective evaluation of colonization with extended-spectrum beta-lactamase-producing Enterobacteriaceae: time course and risk factors

Abstract: We found that prolonged colonization with EPE was common, especially in bedridden patients. Transient negative samples were often observed during the course of colonization. In some patients, urine can be the only positive site from which EPE are isolated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 26 publications
8
16
1
Order By: Relevance
“…In accordance with the carriage studies mentioned above (112,113), we did not find antimicrobial consumption to be correlated with prolonged colonisation. However, there are several studies observing association between previous antimicrobial use and infection with ESBL-E (98,114), and a recent study from the Netherlands also found such a correlation in ESBL-E carriers recruited from a primary health care setting (115).…”
Section: Duration Of Faecal Esbl-e Carriage and Risk Factors For Prolsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with the carriage studies mentioned above (112,113), we did not find antimicrobial consumption to be correlated with prolonged colonisation. However, there are several studies observing association between previous antimicrobial use and infection with ESBL-E (98,114), and a recent study from the Netherlands also found such a correlation in ESBL-E carriers recruited from a primary health care setting (115).…”
Section: Duration Of Faecal Esbl-e Carriage and Risk Factors For Prolsupporting
confidence: 92%
“…The carriage clearance rates we observed were comparable to studies from Sweden (112) and Slovenia (113). We also confirmed the findings from the Swedish study that phylogroup B2, and in our case also phylogroup D, were associated with prolonged carriage.…”
Section: Duration Of Faecal Esbl-e Carriage and Risk Factors For Prolsupporting
confidence: 92%
“…Our major contributors to phylogroups B2/D are ST131 (n = 33) and ST38 (n = 13). In a previous study, ST131 has been associated with prolonged carriage in a cohort of long term health care facility residents [18], while other studies, like the present, do not find this correlation [15,17]. Our observation support the notion that also other strains than ST131 have potential to colonise the human intestine for a long time.…”
Section: Discussionsupporting
confidence: 82%
“…However, they identify different risk factors for prolonged carriage, such as urinary catheter use [16], immobility [17], infection with E . coli strains belonging to phylogroup B2 (which includes ST131) [15,18] and CTX-M group 1 enzymes [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly regarded that in addition to the aforementioned risk factors, outcomes such as length of hospital stay, cost, and death are all adversely affected by MDRO infections, particularly when empiric therapy is not appropriate for pathogen susceptibility. Identified risk factors for MDRO infections include colonization, states of immune compromise (e.g., hemodialysis and transplant recipients), previous antibiotic exposure ranging from three to six months pre-infection, previous hospitalization, and admission from long-term-care facilities [10][11][12][13][14]. The epidemiology behind MDRO infections in both combat-and noncombat-related trauma is poorly understood, given the challenges behind patient enrollment and study design.…”
mentioning
confidence: 99%